GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 12786 species occurrences available in GBIF matching the query: TaxonKey: Phylloscopus trochiloides (Sundevall, 1837). The dataset includes 12786 records from 65 constituent datasets: 606 records from PlutoF platform observations. 1 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 12 records from The avian collection at the Natural History Museum, Oslo, Norway. 140 records from Field Museum of Natural History (Zoology) Bird Collection. 5830 records from Artdata. 1 records from Données ONF Faune-Flore-Fonge. 1 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 105 records from Museum of Comparative Zoology, Harvard University. 1 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 9 records from CAS Ornithology (ORN). 260 records from Bird Ringing Centre in Sweden (NRM). 4091 records from EOD - eBird Observation Dataset. 1 records from iNaturalist Research-grade Observations. 4 records from Aranzadi Ringing Scheme (bird ring-recovery data). 16 records from Birds collection of Yamashina Institute for Ornithology. 3 records from Literature based species occurrence data of birds of North-East India. 1 records from Wirbach-Taubental (Bad Blankenburg). 123 records from naturgucker. 4 records from LACM Vertebrate Collection. 1 records from Birds (NSMK-BI). 65 records from Natural History Museum (London) Collection Specimens. 29 records from Macaulay Library Audio and Video Collection. 1 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 2 records from Birds of Ireland. 19 records from NMNH Extant Specimen and Observation Records. 6 records from Collection Ornithologie - SNSD. 36 records from UWBM Ornithology Collection. 1 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 2 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 4 records from Bird collection of National Museum of Nature and Science. 1 records from MMNH Museum Bird Collection. 130 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 7 records from Biologiezentrum Linz. 3 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 3 records from IndOBIS, Indian Ocean Node of OBIS. 38 records from ORN. 1 records from Aves MZS. 20 records from Naturalis Biodiversity Center (NL) - Aves. 1 records from Schlichemquelle (Tieringen/Meßstetten). 1 records from GEO-Hauptveranstaltung (Insel Vilm). 1 records from Faberpark (Nürnberg/Stein). 1 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 2 records from Natural History Museum, University of Tartu. 1 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 130 records from DOF. 1 records from Biological and palaeontological collection and observation data MNHNL. 2 records from Collection Aves (bird skeletons) SMF. 127 records from DOF 2001-2006. 86 records from AMNH Bird Collection. 1 records from CM Birds Collection. 11 records from Geographically tagged INSDC sequences. 281 records from Norwegian Species Observation Service. 27 records from Animal Sound Archive. 146 records from Estonian Nature Observations Database. 325 records from EBCC Atlas of European Breeding Birds. 5 records from My naturesounds - nature observations with sound recordings. 1 records from Données ONF Faune-Flore-FOnge. 5 records from National System of Protected Areas in Poland - Animals. 23 records from KUBI Ornithology Collection. 9 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 1 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 9 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 1 records from CUMV Bird Collection (Arctos). 9 records from South Australian Museum Australia provider for OZCAM. 1 records from Bird Collection of Museum and Institute of Zoology PAS. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences